2009
DOI: 10.1097/spc.0b013e32832b42ba
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic changes and clinical correlates of advanced dyspnea

Abstract: Purpose of review To discuss the pathophysiology of dyspnea as it relates to patients suffering with chronic respiratory illness or end-stage disease. Recent Findings There are several publications highlighting important new concepts in this field. A new multidimensional model of dyspnea, similar to that developed for pain, sheds new insight into the pathophysiology, while research in pulmonary rehabilitation, exercise testing and distractive auditory stimulation has contributed to our understanding. Finally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Increased ventilatory demand due to interruption of the perfusion capacity in the lung due to vascular obstruction, emboli or the effects of chemotherapy or radiation treatment can also occur. The direct effects of cancer or treatment on the cardio-respiratory or pulmonary system as a result of metastasis, interstitial or vascular complications are shown empirically to cause breathlessness [18]. Secondary mechanisms include skeletal muscle wasting, myopathy of the peripheral muscles, respiratory muscles or myocardium [19] and reduced perfusion capacity as a result of surgical resection of lung tissue [20] or due to comorbid conditions (i.e., COPD) that lead to a further reduction in perfusion capacity or ischemic heart disease and oxygen exchange problems [21].…”
Section: Pathophysiology and Mechanisms For Breathlessnessmentioning
confidence: 99%
“…Increased ventilatory demand due to interruption of the perfusion capacity in the lung due to vascular obstruction, emboli or the effects of chemotherapy or radiation treatment can also occur. The direct effects of cancer or treatment on the cardio-respiratory or pulmonary system as a result of metastasis, interstitial or vascular complications are shown empirically to cause breathlessness [18]. Secondary mechanisms include skeletal muscle wasting, myopathy of the peripheral muscles, respiratory muscles or myocardium [19] and reduced perfusion capacity as a result of surgical resection of lung tissue [20] or due to comorbid conditions (i.e., COPD) that lead to a further reduction in perfusion capacity or ischemic heart disease and oxygen exchange problems [21].…”
Section: Pathophysiology and Mechanisms For Breathlessnessmentioning
confidence: 99%
“…Lifting weights, as part of resistance training, is widely recommended in pulmonary rehabilitation for patients with respiratory disorders [ 23 , 24 ], including those with post-COVID-19 syndrome [ 25 ]. One of the main symptoms of these conditions is dyspnea [ 26 – 28 ], which is associated with increased respiratory effort, decreased ventilation, or both [ 29 ]. Therefore, it seems important to investigate how lung volumes change during postural loading with abdominal bracing in order to determine whether stabilization maneuvers may increase the risk of dyspnea in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…PR consists of physical exercise that is often in combination with patient education and breathing exercises. 11 20 A few studies have investigated the adjuvant effect of adding educational interventions to exercise training, compared to exercise training alone, and found no adjuvant effect. 21 22 However, one Cochrane review found that breathing exercises for patients with COPD had a positive effect on exercise capacity, but there were inconsistent results for effects on dyspnoea and Health-Related Quality of life (HRQL).…”
Section: Introductionmentioning
confidence: 99%